2021
DOI: 10.3389/fphys.2020.622613
|View full text |Cite
|
Sign up to set email alerts
|

Proarrhythmic Electrical Remodeling by Noncardiomyocytes at Interfaces With Cardiomyocytes Under Oxidative Stress

Abstract: Life-threatening ventricular arrhythmias, typically arising from interfaces between fibrosis and surviving cardiomyocytes, are feared sequelae of structurally remodeled hearts under oxidative stress. Incomplete understanding of the proarrhythmic electrical remodeling by fibrosis limits the development of novel antiarrhythmic strategies. To define the mechanistic determinants of the proarrhythmia in electrical crosstalk between cardiomyocytes and noncardiomyocytes, we developed a novel in vitro model of interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 85 publications
1
5
0
Order By: Relevance
“…In initiates proarrhythmic activity (Zhao et al, 2020). In our experiment, we found differences in HR that might reflect H 2 O 2 -mediated heart functionality.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In initiates proarrhythmic activity (Zhao et al, 2020). In our experiment, we found differences in HR that might reflect H 2 O 2 -mediated heart functionality.…”
Section: Discussionsupporting
confidence: 54%
“…It is known that H 2 O 2 is an important factor contributing to the generation of rhythm disturbances and cellular damage during reperfusion of previously ischaemic myocardium. Also, direct application of H 2 O 2 initiates proarrhythmic activity (Zhao et al., 2020 ). In our experiment, we found differences in HR that might reflect H 2 O 2 ‐mediated heart functionality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult mouse CFs (AMCFs) were separated from the ventricle of the MI or sham mice with or without 2-DG treatment on the 28th day after the sham or MI surgery as described previously ( 20 , 21 ). As inadequate cells could be harvested from only one heart, two hearts were isolated together and mixed to produce one group of cardiac cells with an enzymolysis approach.…”
Section: Methodsmentioning
confidence: 99%
“…We demonstrated that the point-to-point, single-sided CM-MF connection impaired the impulse propagation of the CM monolayers. The single-sided CM-MF connection model was also studied using a linear connection model between monolayers of CMs and MFs with Cx43 without the insertion or mixture of these two types of cells (Zhao et al, 2020). Under such a linear interface, the authors observed the spontaneous occurrence of re-entrant arrhythmias in the CM monolayer after the application of hydrogen peroxide by prolonging the action potential duration (Zhao et al, 2020).…”
Section: Pathophysiological Significance Of Cx43 Gap-junctional Conne...mentioning
confidence: 99%